SERUM FERRITIN AND HbA1c LEVELS IN TYPE 2 DIABETES MELLITUS - P, Padmaja; S, Shabana; Mas, Shariq (International Journal of Clinical and Biomedical Research, 2015)
Introduction: Complications due to diabetes are a major cause of disability, reduced quality of life and death. Recent studies have emphasized the role of serum ferritin in insulin resistance and the incidence of diabetes mellitus. However, the role of ferritin as a marker of iron overload in pancreatic damage and peripheral insulin resistance or its role as an inflammatory marker is not clear. The aim of this study is to establish a correlation between serum ferritin, FBS and HbA1c in type 2 diabetes mellitus and to evaluate the role of serum ferritin on the glycemic status in type 2 diabetes mellitus. Methods: This was a cross- sectional study of 100 cases, visiting medical outpatient department of a tertiary care teaching hospital. Diabetic patients were compared with age and sex matched normal healthy controls. Effect of serum ferritin on glycemic status, gender and age was noted.Â Results: Statistically significant increase of FPG, HbA1C and serum ferritin levels were observed in type 2 diabetes mellitus group than controls in both females and males while there was no statistically significant difference of hemoglobin between diabetic group and controls in females and males. There was a high (r= 0.62, r= 0.66) positive correlation between SF and HbA1c of females and males respectively in diabetic group P-value=< 0.01. Conclusion: Higher positive correlation of serum ferritin with HbA1c shows that hyperglycemia affects ferritin levels possibly due to inflammation or oxidative stress or a combination of the two. KEYWORDS: Type 2 diabetes mellitus; Glycosylated haemoglobin; Ferritin.